Serum high sensitivity C-reactive protein in breast cancer patients - Asegaonkar, Shilpa Balaji; Takalkar, Unmesh Vidyadhar; Kodlikeri, Pushpa; Pagdhune, Avinash; Bonduliya, Virendrakumar; Thorat, Anand Pandurang (International Journal of Research in Medical Sciences, 2017)
Background:Breast cancer, second commonest malignancy in women is a multifactorial disease. Key role of chronic low grade inflammation has been linked with pathophysiology of breast cancer. High sensitivity C-Reactive Protein (hsCRP) is an acute phase reactant proinflammatory protein synthesized in hepatocytes. Present case control study was aimed with primary objective of estimation of serum hsCRP levels in newly diagnosed breast cancer patients and to correlate them with the staging of the disease. Methods:We enrolled 60 newly histologically diagnosed cases of breast cancer and 60 healthy age matched controls. Demographic features, anthropometric measures were recorded. After overnight fast, blood samples were collected and analyzed for serum hsCRP levels. Results:We observed significant differences between cases and controls in anthropometric parameters BMI and waist: hip (P <0.05) and hsCRP levels (P <0.001). Depending of the stage, serum hsCRP levels were associated with advanced stage. In stage I, association of hsCRP was not significant with disease while in stage II and III there was significant association. In stage IV patients with distant metastasis, serum hsCRP values were highly significantly raised compared to stage II and III. This suggests significant association of state of inflammation with stage of breast cancer. Conclusion:Inflammatory component plays key role in all stages of tumourigenesis from initiation of the tumor, infiltration, local and systemic invasion. Estimation of hsCRP may be simple, inexpensive and useful tool for risk assessment, screening of high risk individuals and to predict outcome in diagnosed cases.